Cultivo de Streptococcus pyogenes vs prueba de inmunoensayo cualitativa en pacientes con exudado faríngeo que acuden al Hospital Isidro Ayora de Loja - Díaz Sinche, Fabián Darío (2019)
The present investigation whose subject "STREPTOCOCCUS PYOGENES CULTURE VS QUALITATIVE IMMUNOASSAY TEST IN PATIENTS WITH PHARYNGEAL EXUDATE WHO VISIT THE ISIDRO AYORA DE LOJA HOSPITAL", was carried out at the Isidro Ayora hospital located in the city of Loja. Its objective was to permit a comparative analysis between the culture test and the qualitative immunochromatographic test to establish the sensitivity and specificity in the detection of streptococcus pyogenes in pharyngeal exudate samples of patients who visit the Isidro Ayora hospital laboratory. The culture test and immunochromatographic test were applied; culture is a method used for the multiplication of microorganisms such as bacteria and is considered a fundamental method for the identification of streptococcus pyogenes, giving reliable results. The rapid cassette test is a qualitative immunochromatographic assay for the detection of the streptococcal A carbohydrate antigen, in throat swabs, which provides immediate results, contributing to a rapid and reliable diagnosis. The results obtained indicate that there is a sensitivity of 50% and a specificity of 98% from the rapid immunochromatographic test compared to the culture test with a sensitivity of 100% and a specificity of 100%. Based on the results, it is inferred that the rapid test is a simple and effective method to make an adequate diagnosis of streptococcal pharyngitis in ambulatory consultations. Key words: Streptococcus pyogenes - culture - immunochromatographic test - pharyngeal exudate - sensitivity - specificity.